Country driving a Chinese road trip = Xun lu Zhongguo - Hessler, Peter 1969- (Canongate, 2010)
In the summer of 2001, Peter Hessler, the longtime Beijing correspondent for The New Yorker, acquired his Chinese driver's license. For the next seven years, he traveled the country, tracking how the automobile and improved roads were transforming China. Hessler writes movingly of the average people farmers, migrant workers, entrepreneurs who have reshaped the nation during one of the most critical periods in its modern history. Country Driving begins with Hessler's 7,000-mile trip across northern China, following the Great Wall, from the East China Sea to the Tibetan plateau. He investigates a historically important rural region being abandoned, as young people migrate to jobs in the southeast. Next Hessler spends six years in Sancha, a small farming village in the mountains north of Beijing, which changes dramatically after the local road is paved and the capital's auto boom brings new tourism. Finally, he turns his attention to urban China, researching development over a period of more than two years in Lishui, a small southeastern city where officials hope that a new government-built expressway will transform a farm region into a major industrial center